Salmonella serogroups identified from adult diarrhoeal out-patients in Addis Ababa, Ethiopia: antibiotic resistance and plasmid profile analysis. - Mache, A; Mengistu, Y; Cowley, S (1997)
Forty five Salmonella strains were isolated from 700 diarrhoeal samples collected from adult diarrhoeal out-patients in Addis Ababa. Among the isolates, serogroup C comprised 31.1%, B 24.4%, S.typhi 15.6%, D 13.3%, A 8.9% and E 6.7%. Among the isolates, 71.1% were resistant to tetracycline, 68.9% to ampicillin, 66.7% to cephalothin, 57.8% to trimethoprim-sulphamethoxazole, 53.9% to kanamycin, 46.7% to chloramphenicol and less than 31.8% of the isolates were resistant to other drugs. Among S.typhi isolates, 28.6% were resistant to chloramphenicol and this shows the emergence of chloramphenicol resistant S.typhi strains in Ethiopia. Gentamicin and polymyxin B were found to be the drugs of choice for cases of salmonellosis including S.typhi. All drug resistant isolates analysed for plasmids contained multiple plasmids ranging in sizes from 1.8 to greater than 21 Kilobases.